2014
DOI: 10.1186/1475-2891-13-57
|View full text |Cite
|
Sign up to set email alerts
|

Impact of daily Chlorella consumption on serum lipid and carotenoid profiles in mildly hypercholesterolemic adults: a double-blinded, randomized, placebo-controlled study

Abstract: BackgroundHigh level of serum cholesterol is considered to be a major risk factor for cardiovascular disease (CVD). A double-blinded, randomized, placebo-controlled trial was performed to test the hypothesis that a daily intake of Chlorella may improve serum lipid profile through enhancement of serum carotenoid concentration in mildly hypercholesterolemic subjects.MethodsEligible subjects (n = 63) were randomized to either Chlorella (5 g/day) or placebo for a double-blinded trial with a 2-week lead-in period a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 32 publications
2
30
0
3
Order By: Relevance
“…The present study is the first evidence to confirm that regular consumption of newly made beverage reduces body weight, body fat mass (Beh et al, 2017;Kondo et al, 2009;Park et al, 2014;Ryu et al, 2014;Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The present study is the first evidence to confirm that regular consumption of newly made beverage reduces body weight, body fat mass (Beh et al, 2017;Kondo et al, 2009;Park et al, 2014;Ryu et al, 2014;Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, continuous beverage consumption was found to lower serum lipid profile, serum leptin, aspirate transaminase, alanine transaminase, urea, and creatinine levels. While similar anti‐obesity and anti‐hypercholesterolemic actions were demonstrated in the polyphenols or vinegar containing foods or their products (Beh et al, ; Kondo et al, ; Park et al, ; Ryu et al, ; Wang et al, ). These outcomes can be deliberated to be due to the lessening in body fat mass triggered by beverage consumption, because the TFA, VFA, and SFA values were lesser in the beverage group as related to placebo.…”
Section: Discussionmentioning
confidence: 72%
“…Dates and garlic are significant sources of carotenoids and considerably enhance the serum concentration of b-carotenoid. While, results of one study also showed that ingestion of Chlorella (5 g/day) increased the concentration of carotenoids in hypercholesterolemic adults (n 5 63) (Ryu et al, 2014). Carotenoid and dietary lipid absorption follow the same steps: discharge from the food milieu, solubilization in miscellaneous micelles, excretion into the lymphatic order, and packing into chylomicrons (Erdman, Bierer, & Gugger, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…While similar anti‐hyperlipidemic and hypotensive actions were demonstrated in the polyphenols or vinegar containing foods or their products. Ryu et al () revealed that daily consumption of 5 g of Chlorella for 6 weeks significantly reduced the TC, TG and carotenoids concentrations of subjects with hyperlipidemia ( n = 63). Davies et al () showed reductions in LDL‐C 11.1%, TC 6.5%, lipoprotein A 16.4% and apolipoproteins B 5% concentrations after intake of 5 servings/day of black tea as compared with placebo in subjects with mild hypercholesterolemia ( n = 15).…”
Section: Discussionmentioning
confidence: 98%
“…Серед них полісахариди (альгінати, фукоїдан, ламінарин, агар, манан тощо) (Kim, 2013;Park, 2015), пігменти (хлорофіли, фікобіліни, каротиноїди, лютеїн тощо) (El Gamal, 2010;Michalak & Chojnacka, 2015), ліпіди (насичені жирні кислоти та цінні поліненасичені жирні кислоти (C 20:5, n-3 , C 22:6, n-3 , C 18:3, n-6 ) (Chen & Chou, 2002;Haq et al, 2011), бетаїни, поліаміни, стерини, фітогормони (Lu & Xu, 2015), пептиди та протеїни, поліфеноли та їх похідні (Harnedy & Fitzgerald, 2011), а також основні вітаміни та мінерали (Croft et al, 2006;Tang & Suter, 2011). Щодо тварин і людини, то для багатьох цих сполук властивий широкий спектр потенційних лікувально-профілактичний властивостей: антиоксидантні (Fernando et al, 2016;Lukashiv et al, 2016), протиракові, антивірусні, антикоагулянтні, антибактеріальні (Bellou et al, 2014), антиалергічні, антидіабетичні, протизапальні та антигіпертензивні властивості (Lee & Kim, 2009;Ryu et al, 2014;Kim et al, 2016).…”
unclassified